A revision of Hydraena species of the “Haenydra” lineage (Coleoptera, Hydraenidae) - Trizzino, Marco; Carnevali, Lucilla; de Felici, Stefano; Audisio, Paolo (Zootaxa, 2013)
Hydraena Kugelann represents the largest genus within the water beetle family Hydraenidae, and in particular within Hydraeninae, with about 900 species widely distributed all over the world and several hundreds not yet described. In a recent cladistic analysis, based on morphological characters, Hydraena s. l. was split into two subgenera: Hydraenopsis Janssens (Gondwanian) and Hydraena s. str. (Laurasian). Moreover, within Hydraena s. str., some derived and well-supported monophyletic clades were recognised, and defined as “lineages”. Among them, the "Haenydra" lineage, previously considered by many authors as a valid genus/subgenus, includes 89 species distributed exclusively in western Palaearctic, from Portugal to Iran, but absent in North Africa. The main aim of the present paper is to provide a revision of the whole lineage, re-examining taxonomy, ecology, and biogeography of all known species. All species were therefore redescribed, also providing information about diagnostic characters, taxonomic and phylogenetic relationships, ecology and biogeography. A faunistic dataset, including all the known published, and many unpublished, localities for each species, with a series of detailed geographic maps for each species and species complex, was herein supplied. Finally, dichotomous keys are provided for identification of males of all the "Haenydra" species.